(untitled) (The International Research Journal of Management Science, 2021)
Purpose: The purpose of this study is to identify the behavioral factors influencing individual investors’ decisions and to analyze the relationship between these factors and investment decision performance. Design/Methodology/Approach: The tested variables were: Anchoring bias, Gambler’s Fallacy, Overconfidence bias, Availability and Representativeness bias from heuristics factor, Mental Accounting, Loss and Regret Aversion from prospect factor, and Market variables and Herding factors. The study employed exploratory and confirmatory factor analysis. In addition, structural equation modeling is applied for the testing of the hypotheses. Findings: Prospect behavioral factor is seen to have negative correlation to investment performance. Herding, Market variables and Heuristic (including overconfidence and anchoring bias) are found to have positive correlation to investment performance. Implications: To cope with intense competition among the competitors in Nepali stock market, this study provides strong evidence herding and heuristic approach that have positive indication to investment performance